Analysis of the results of the study of reading skills formation in younger students of russian-language schools in Almaty - Абишева, Сауле; Поляк, Зинаида; Асылбекова, Марина; Сабирова, Дина; Абаева, Мадина (Pedagogy and Psychology, 2020)
The assessment of progress in learning to read, carried out among first-graders of 11 Russian-teaching schools in Almaty, was in-depth and included a comprehensive system for assessing child development. This system connects different results obtained in different evaluative sections: educational, metasubject, individual and personal. Two cognitive assessment tools were administered to diagnose children: a vocabulary test and a multi-task reading test. The test for the diagnosis of early reading skills consists of four blocks corresponding to the four stages of development of reading skills in children. The analysis of the scale within the framework of modern testing theory allows for a deep analysis of the characteristics of the functioning of individual tasks and the test as a whole, as well as obtaining measurement results on an interval scale. The most important results of the initial analysis of the assessment results were the absence of differences in reading skills between girls and boys who came to school, and the advantage of boys on the vocabulary scale. The analysis carried out will make it possible to clarify the content of further stages of the study in order to explain the results obtained and interpret them meaningfully.